Francisco Alberdi, Christian Nørregaard, Marianne Kastrup, Majken Kristensen (red.): Transkulturel psykiatri - Johansen, Katrine S.; Jacobsen, Charlotte (Tidsskriftet Antropologi, 2002)
Anmeldes af Katrine S. Johansen og Charlotte Jacobsen